Effects of Problem-Based Learning on Elementary Students’ Scientific Literacy: A Quasi-Experimental Study - Juliana Dadiara; Marleny Leasa; John Rafafy Batlolona (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study investigated the effect of Problem-Based Learning (PBL) on elementary school students’ scientific literacy in ecosystem learning. A quasi-experimental pretest–posttest non-equivalent control group design was employed involving 32 fifth-grade students from two primary schools in Ambon City, Indonesia. The experimental group consisted of 20 students from SD Negeri 76 Ambon, while the control group consisted of 12 students from SD Inpres 45 Ambon. The intervention was implemented over four weeks (eight lessons, 70 minutes each). The experimental group was taught using a structured seven-stage PBL model, whereas the control group received conventional teacher-centered instruction. Scientific literacy was assessed using an eight-item essay test aligned with PISA-oriented indicators, namely explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting data and evidence. The instrument demonstrated acceptable validity (r = 0.70) and reliability (Cronbach’s α = 0.84). Data analysis using an independent samples t-test revealed a statistically significant difference between groups (t = −2.692, p = 0.012). Students in the PBL group achieved substantially higher posttest scores (M = 70.00, SD = 8.41) than those in the conventional group (M = 54.00, SD = 7.96), indicating a meaningful instructional effect. Further analysis showed that PBL particularly strengthened students’ abilities to interpret data and construct evidence-based explanations. These findings suggest that PBL is an effective instructional approach for enhancing scientific literacy in elementary ecosystem learning contexts, although conclusions should be limited to similar classroom settings and sample characteristics.